The Role of Art in the Formation of Social Identity and the Maintenance of Ethnic Boundaries - Borjan, Etami (2009)
The paper focuses on the ways in which Italians form their new multi-ethnic identity through art (music) that becomes a very strong tool for the conscious construction of social identity.Two documentaries, L’ orchestra di Piazza Vittorio (2006), and Nazirock (2008), show how contemporary Italian society copes with cultural distinctiveness.The first film is an example of interethnic dialogue and cultural exchange among musicians from all over the world playing in a multi-ethnic orchestra in Rome.The second film shows Italian Fascist groups and new underground Fascist rock scene.The use of presumably typical ethnic symbols, political rhetoric and everyday practices in music stresses cultural distinctiveness between Italians and immigrants.The films demonstrate two tendencies in contemporary Italian society ; willingness to broaden national identity boundaries by creation of one shared culture and refusal to transcendent social ethnic boundaries through interaction with “ others” .They also reveal the importance of the relationship between ideology, social practices and culture in the formation of new Italian nationhood.